Learning to Love - Wilson, J. author. aut Link
XIV, 301 p.
Keywords: Nobody thinks love unimportant, but we are not as clear as we should be about what love involves, and about what it is to learn to love. This book is primarily concerned with personal love between the sexes (or between members of the same sex). It is a mixture of analytic philosophy and depth-psychology, but free from jargon and technicality. Its main aim is to help us to understand the nature and value of love, and to grasp the difficulties we have to face when engaging with it.